Expanding the Molecular Landscape of Androgen Insensitivity Syndrome Through Next-Generation Sequencing - Kałużewski T; Pinkier I; Wysocka U; Sałamunia J; Kępczyński Ł; Piotrowicz M; Kałużewski B; Gach A (The Application of Clinical Genetics)
Tadeusz Kałużewski,1,2 Iwona Pinkier,1 Urszula Wysocka,1 Jordan Sałamunia,2 Łukasz Kępczyński,1,2 Małgorzata Piotrowicz,1 Bogdan Kałużewski,2 Agnieszka Gach1 1Department of Genetics, Polish Mother’s Memorial Hospital Research Institute, Lodz, 93-338, Poland; 2R&D Division, Laboratory of Medical Genetics, GENOS Sp. z o.o., Lodz, 91-033, PolandCorrespondence: Tadeusz Kałużewski, Email tadeusz.kaluzewski@iczmp.edu.plAbstract: Androgen insensitivity syndrome (AIS) is an X-linked genetic disorder caused by mutations in the androgen receptor gene (AR), leading to impaired androgen signaling and resulting in varying degrees of undermasculinization in individuals with a 46,XY karyotype. This study aimed to expand the molecular landscape of AIS by identifying and characterizing pathogenic variants in the AR gene via next-generation sequencing (NGS). Molecular diagnostics revealed eight distinct variants within the AR gene, two of which had not been previously described. These include the following novel variants: c.3G>A, and c.1344_1345insTA. This study broadens the spectrum of known AR gene mutations associated with AIS and highlights the critical role of molecular diagnostics in the accurate classification of variants. These findings will aid in enhancing the clinical management and genetic counseling of individuals affected by AIS.Keywords: androgen insensitivity syndrome, AIS, androgen receptor gene, AR gene, next-generation sequencing, NGS, disorders of sex development, complete androgen insensitivity syndrome, CAIS